Pemanfaatan Bonggol Pisang Sebagai Keripik Untuk Meningkatkan Nilai Jual Produk Dengan Pemasaran Berbasis Digital - Pambudi, Muhammad; Suprayitno, Suprayitno; Syahrial, Yoppi (Edumedia Solution, 2023)
Banana hump is rarely used as an ingredient in foods like chips. Currently, the marketing of banana hump chips is ineffective and constrained. Banana hump processing into chips and digital-based marketing of banana hump chips are used in PKKM MBKM entrepreneurial operations. Activities related to PKKM MBKM are conducted for three months. Banana hump chips are made by slicing the hump, soaking it in whiting, grinding the seasoning ingredients, forming the seasoning dough, frying, draining the oil, and packaging. The Gofood and Shopee programs are used for online marketing of banana hump chips.